2021
DOI: 10.1002/er.7108
|View full text |Cite
|
Sign up to set email alerts
|

Economic‐environmental stochastic scheduling for hydrogen storage‐based smart energy hub coordinated with integrated demand response program

Abstract: According to the necessity of establishing an effective, dependable, and costeffective system to supply various demands, the significance of an energy hub has emerged in recent years. Also, the other aspect dealing with decreasing the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 52 publications
(89 reference statements)
0
14
0
Order By: Relevance
“…In general, the output power of a wind turbine has a non‐linear relationship with wind speed. Therefore, we use from () to convert wind speeds to power [43]. Pt,sWT=left0Vt,sWT<VCIleftPWT,Max0trueVt,sWTVCIVRVCI3VCIgoodbreak≤Vt,sWT<VRleftPWT,MaxVRgoodbreak≤Vt,sWT<VCOleft0Vt,sWTVCO$$\begin{eqnarray} P_{t,s}^{WT} = \left\{ \def\eqcellsep{&}\begin{array}{l} 0 \def\eqcellsep{&}\begin{array}{*{20}{c}} {}&{}&{ \def\eqcellsep{&}\begin{array}{*{20}{c}} {}&{}&{ \def\eqcellsep{&}\begin{array}{*{20}{c}} { \def\eqcellsep{&}\begin{array}{*{20}{c}} {}&{} \end{array} }&{} \end{array} } \end{array} }&{V_{t,s}^{WT}} \end{array} &lt; {V}^{CI}\\[15pt] {P}^{WT,Max}{\left( {\dfrac{{V_{t,s}^{WT} - {V}^{CI}}}{{{V}^R - {V}^{CI}}}} \right)}^3 \def\eqcellsep{&}\begin{array}{*{20}{c}} {}&{{V}^{CI} \le V_{t,s}^{WT} &lt; {V}^R} \end{array} \\[15pt] {P}^{WT,Max} \def\eqcellsep{&}\begin{array}{*{20}{c}} { \def\eqcellsep{&}\begin{array}{*{20}{c}} { \def\eqcellsep{&}\begin{array}{*{20}{c}} {}&{} \end{array} }&{} \end{array} }&{}&{}&{{V}^R \le V_{t,s}^{WT} &lt; {V}^{CO}} \end{array} \\[15pt] 0 \def\eqcellsep{&}\begin{array}{*{20}{c}} { \def\eqcellsep{&}\begin{array}{*{20}{c}} { \def\eqcellsep{&}\begin{array}{*{20}{c}} {}&{ \def\eqcellsep{&}\begin{array}{*{20}{c}} {}&{} \end{array} } \end{array} }&{}&{} \end{array} }&{}&{}&{V_{...…”
Section: Proposed Frameworkmentioning
confidence: 99%
See 2 more Smart Citations
“…In general, the output power of a wind turbine has a non‐linear relationship with wind speed. Therefore, we use from () to convert wind speeds to power [43]. Pt,sWT=left0Vt,sWT<VCIleftPWT,Max0trueVt,sWTVCIVRVCI3VCIgoodbreak≤Vt,sWT<VRleftPWT,MaxVRgoodbreak≤Vt,sWT<VCOleft0Vt,sWTVCO$$\begin{eqnarray} P_{t,s}^{WT} = \left\{ \def\eqcellsep{&}\begin{array}{l} 0 \def\eqcellsep{&}\begin{array}{*{20}{c}} {}&{}&{ \def\eqcellsep{&}\begin{array}{*{20}{c}} {}&{}&{ \def\eqcellsep{&}\begin{array}{*{20}{c}} { \def\eqcellsep{&}\begin{array}{*{20}{c}} {}&{} \end{array} }&{} \end{array} } \end{array} }&{V_{t,s}^{WT}} \end{array} &lt; {V}^{CI}\\[15pt] {P}^{WT,Max}{\left( {\dfrac{{V_{t,s}^{WT} - {V}^{CI}}}{{{V}^R - {V}^{CI}}}} \right)}^3 \def\eqcellsep{&}\begin{array}{*{20}{c}} {}&{{V}^{CI} \le V_{t,s}^{WT} &lt; {V}^R} \end{array} \\[15pt] {P}^{WT,Max} \def\eqcellsep{&}\begin{array}{*{20}{c}} { \def\eqcellsep{&}\begin{array}{*{20}{c}} { \def\eqcellsep{&}\begin{array}{*{20}{c}} {}&{} \end{array} }&{} \end{array} }&{}&{}&{{V}^R \le V_{t,s}^{WT} &lt; {V}^{CO}} \end{array} \\[15pt] 0 \def\eqcellsep{&}\begin{array}{*{20}{c}} { \def\eqcellsep{&}\begin{array}{*{20}{c}} { \def\eqcellsep{&}\begin{array}{*{20}{c}} {}&{ \def\eqcellsep{&}\begin{array}{*{20}{c}} {}&{} \end{array} } \end{array} }&{}&{} \end{array} }&{}&{}&{V_{...…”
Section: Proposed Frameworkmentioning
confidence: 99%
“…Equations ( 41) and ( 42) illustrate the communication between the input and output of the TBESs to each bus. Finally, (43) guarantees that the TBESs will stop for hours after arriving at the bus.…”
Section: Tbes Constraintsmentioning
confidence: 99%
See 1 more Smart Citation
“…In response to the growing demand for reliable electricity generation from the utilization of renewable energy resources in electricity markets, more attention has been put on renewable energy integration with DR. Masoud et al 19 investigated a smart multicarrier energy hub including DR and hydrogen storage system and found that the utilization of DR and hydrogen storage system could decrease overall cost and total emission. The effect of DR on the size optimization of a stand‐alone integrated renewable energy system was analyzed by using a discrete harmony search algorithm in Reference 20, and the simulation results showed a significant reduction in system sizes and costs.…”
Section: Introductionmentioning
confidence: 99%
“…17 Hydrogen also has an economic advantage over batteries in terms of long-term storage. 18 The productions and applications of hydrogen in various fields are shown in Figure 1. According to Figure 1, hydrogen is used in storage systems, fossil fuels, power generation, heating, the petrochemical industry, and transportation.…”
Section: Introductionmentioning
confidence: 99%